Revitalizing local wisdom values in Nandong Smong musical: Strengthening educational materials in Gen Z - Hakim, Putri Rahmah Nur; Pabbajah, Mustaqim; Wisetrotomo, Suwarno; Andiko, Benny; Sari, Intan Permata (Institut Seni Indonesia Yogyakarta, 2025)
This study explores the cultural and educational significance of Nandong Smong, a traditional oral literature form from Simeulue Island, Indonesia, which functions as both a disaster narrative and a medium of intergenerational knowledge transfer. The objective of this research is to analyze the lyrical content and sociocultural meaning embedded in the Smong song to understand its role in tsunami preparedness and collective memory among Simeulue communities. The study employed a qualitative approach, with data collected through direct observation in Simeulue and in-depth interviews with several local elders, who were asked to interpret the meanings and messages of the Smong lyrics. These primary data sources were supported by secondary data obtained from YouTube, where Smong songs were transcribed and examined word-by-word for textual analysis. The results reveal that Nandong Smong is not merely an artistic expression but a crucial oral tradition rooted in the island’s historical experience of the 1907 tsunami. The lyrics contain warnings, survival strategies, and moral teachings that emphasize local wisdom, memory, and collective responsibility. Furthermore, the discussion highlights the effectiveness of oral literature in shaping communal resilience and transmitting indigenous knowledge through non-formal education. The conclusion emphasizes the need to preserve Nandong Smong as both an intangible cultural heritage and an alternative model for disaster education. This research implies that integrating local narratives into disaster risk reduction strategies may enhance community preparedness in disaster-prone areas. Therefore, it is recommended that policymakers and educators consider incorporating oral traditions such as Nandong Smong into formal educational curricula and community-based disaster awareness programs.